تأثير التغذية الطبيعية والإضافية في طوائف تربية ملكات نحل العسل (Apis mellifera L.) في محافظة اللاذقية _ سورية. - مكيس, خليل; رمضان, علي; غزالة, ديما (Latakia University Journal -Biological Sciences Series, 2019)
This study was carried out in the Karsana near ​​Lattakia, Syria, within a citrus grove. Various food mixes were tested to see their effect on the strength and productivity of honey bee colonies from queens. The results of the study during the extended feeding period from 10/3/2018 to 30/6/2018, showed that additional protein feeding (pollen substitutes :a mixture of local bean flour, wheat flour, crushed sugar, vitamin C, at ratio (2: 1: 3) Respectively), was significantly higher for both sugary solution feeding and control; in terms of average strength of colonies which reached 14 frame/colony, sugary solution feeding was 10 frame/colony, while control reached 9 frame/colony. As for The average percentage of grafted larvae acceptance was 86.6%, 70% and 63.6% for both protein and sugary feeding and control, respectively. In terms of average weight of virginal queens resulting from the grafting process, the queens obtained from protein feeding achieved =209.84 mg, followed by the sugary yeast queen =198.81 mg, and control that achieved =197.89 mg. نفذت هذه الدراسة في منطقة كرسانا التابعة لمحافظة اللاذقية، سورية؛ ضمن بستان مزروع بالحمضيات، وتم اختبار خلطات غذائية مختلفة لمعرفة تأثيرها على قوة طوائف نحل العسل وإنتاجيتها من الملكات. أوضحت نتائج الدراسة خلال فترة التغذية الممتدة من 2018/3/10 ولغاية 2018/6/30، أن التغذية الإضافية البروتينية ببدائل حبوب اللقاح (خلطة مكوّنة من دقيق الفول البلدي- دقيق القمح-سكر مطحون- فيتامينC بنسبة (2:1:3) على التوالي)، قد تفوّقت معنوياً على كل من التغذية بالمحلول السكري والشاهد؛ من حيث متوسط قوة الطوائف الذي بلغ 14 إطار/طائفة أما التغذية بالمحلول السكري فقط، فقد بلغ 10 إطار/طائفة، بينما بلغ العدد في معاملة الشاهد 9إطار/طائفة. أما بالنسبة لمتوسط النسبة المئوية لقبول اليرقات المطعَّمة؛ فقد كانت86.6 % = و 70% = و 63.6% = لكل من التغذية البروتينية والسكرية والشاهد على التوالي. ومن حيث متوسط وزن الملكات العذارى الناتجة عن عملية التطعيم؛ فقد حققت الملكات الناتجة عن التغذية البروتينية متوسط وزن مقداره 209.84 ملغ، تليها الملكات الناتجة عن التغذية السكرية 198.81 ملغ، ثم الشاهد التي حققت 197.89 ملغ.